2017
DOI: 10.1177/0959683616687387
|View full text |Cite
|
Sign up to set email alerts
|

Very low inheritance in cosmogenic surface exposure ages of glacial deposits: A field experiment from two Norwegian glacier forelands

Abstract: Terrestrial cosmogenic nuclide dating has been widely used to estimate the surface exposure age of bedrock and boulder surfaces associated with deglaciation and Holocene glacier variations, but the effect of inherited age has been rarely directly addressed. In this study, small clasts, embedded in flute surfaces on two cirque glacier forelands in Jotunheimen, southern Norway and deposited within the last ~60 years, were used to test whether such clasts have the modern surface exposure age expected in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The knowledge of the vertical dimension of the LGM ice sheet could provide crucial information on palaeoenvironmental factors like sea-level changes, atmospheric and oceanic circulation, (de-)glaciation patterns, icesheet erosion rates, landscape evolution, and englacial thermal boundaries (Winguth et al, 2005;Rinterknecht et al, 2006;Goehring et al, 2008). The interpretation of bedrock with different degree of weathering in mountain areas affected by Quaternary glaciation can, therefore, be important for determining ice-sheet behaviour and thickness during the last glaciation periods (Brook et al, 1996;Briner et al, 2006;McCarroll, 2016). There are several concepts to explain the limit between differently weathered bedrock (trimline) separating highly weathered uplands comprising blockfields and tors from relatively unweathered lower exposures of freshly eroded glacial features (Rea et al, 1996;Briner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the vertical dimension of the LGM ice sheet could provide crucial information on palaeoenvironmental factors like sea-level changes, atmospheric and oceanic circulation, (de-)glaciation patterns, icesheet erosion rates, landscape evolution, and englacial thermal boundaries (Winguth et al, 2005;Rinterknecht et al, 2006;Goehring et al, 2008). The interpretation of bedrock with different degree of weathering in mountain areas affected by Quaternary glaciation can, therefore, be important for determining ice-sheet behaviour and thickness during the last glaciation periods (Brook et al, 1996;Briner et al, 2006;McCarroll, 2016). There are several concepts to explain the limit between differently weathered bedrock (trimline) separating highly weathered uplands comprising blockfields and tors from relatively unweathered lower exposures of freshly eroded glacial features (Rea et al, 1996;Briner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Field experiments and selected tests have persuasively shown that the zero-age assumption (i.e. fulfillment of the 'no-inheritance' requirement) with the cosmogenic nuclide dating of rock fragments recently deposited at modern temperate glaciers is a valid one (Putnam et al 2012;ScHimmelPfenniG et al 2014;mattHeWS et al 2017). ScHaefer et al (2009) come to the same conclusion, yet surprisingly miss to draw related consequences for the procedure to obtain their final age estimates for boulder clusters.…”
Section: Geomorphological Interpretation Of Numerical Boulder Agesmentioning
confidence: 97%